Characterization of the contribution of S-nitrosylated proteins to the aggregation of alpha-synuclein in Parkinson´s Disease - Teixeira, Mariana Filipa Fernandes (2024)
Alpha-synuclein (-Syn) is present in Lewy Bodies and its aggregation has been associated with Parkinson's disease (PD). However, the cause of -Syn aggregation is unknown. An increase in reactive nitrogen species (RNS) in PD has been described, which can lead to oxidative posttranslational modifications such as S-nitrosylation. This chemical process involves the covalent attachment of a nitric oxide group (NO) to a cysteine thiol within a protein to generate an S-nitrosothiol (SNO). Because it does not have cysteine residues in its structure, -Syn is not a direct target of S-nitrosylation. When S-nitrosylated, enzymes such as protein disulfide isomerase (PDI) and serine racemase (SR) can cause misfolded proteins to aggregate. Nonetheless, no research has been conducted to determine how S-nitrosylation of these proteins is involved in -Syn aggregation. The current study aimed to determine how S-nitrosylation in the proteome, induced by CysNO treatment, affects -Syn aggregation and cell viability by examining the presence of -Syn aggregates and cleaved caspase-3 in SH-SY5Y cells expressing WT, A53T, or A30P -Syn. The western blot results indicate that PDI is indeed S-nitrosylated. However, SR was not proven to be S-nitrosylated. These results indicate that only one protein (PDI) may contribute to the aggregation process of - Syn. Using the immunocytochemistry technique, the percentage of transfected cells, the number of transfected cells with aggregates, the presence of cleaved caspase-3 (an indicator of cell death) and the presence of condensed/fragmented nuclei were quantified. These results showed that S-nitrosylation increases aggregation of -Syn, depending on its form. And that the amount of cytotoxicity present in cells exposed to CysNO is not significant. These studies suggest that S-nitrosylation may increase the aggregation process of -Syn. Future studies could elucidate a cause-effect between the nitrosylation of proteins such as PDI and the aggregation of -Syn.